Dispensing of potentially teratogenic drugs before conception and during pregnancy: a population‐based study. (15th October 2014) - Zomerdijk, IM; Ruiter, R; Houweling, LMA; Herings, RMC; Straus, SMJM; Stricker, BH
<x xml:space="preserve">Abstract</x> Objective To study the dispensing of potentially teratogenic drugs in the 12‐month period before as well as during pregnancy in the Netherlands. Design Population‐based study. Setting A cohort was constructed using a linkage between the PHARMO Database Network and the Netherlands Perinatal Registry (PRN). Population A total of 203 962 Dutch pregnancies reported between 1999 and 2007 Methods Drug‐dispensing information was identified from the PHARMO Database Network for the 12‐month period before conception and during pregnancy. Drugs with either a Swedish FASS 'D' classification, an Australian ADEC or American FDA 'D' or 'X' classification were considered potentially teratogenic (n = 202). Mean outcome measures Proportion of pregnancies that received potentially teratogenic drugs in the 12‐month period before and during pregnancy and specific for the risk category X drugs and newly initiated drugs. Results Sixteen percent of the pregnancies received a potentially teratogenic drug in the 12‐month period before and 5.07% during pregnancy. Doxycycline and paroxetine were most frequently received during pregnancy by 1.01% and 0.85% of women, respectively; 0.66% of the women received a risk category X drug during pregnancy which most frequently consisted of triptorelin (0.25%), norethisterone (0.22%) and simvastatin (0.03%). Fifty‐three percent of the women who received a potentially teratogenic drug during pregnancy received this for the first time during the study period. These percentages were heterogeneous between therapeutic drug classes. Conclusions Five percent of the pregnancies received a potentially teratogenic drug during pregnancy and 0.66% received a drug from the risk category X. It may be possible to reduce these proportions when reasons for prescription have been explored.